Description of Emotional on Child Patients with Epilepsy at H. Adam Malik General Hospital Medan - Panjaitan, Cornelia Rosa Liliani; Sain, Johannes H.; Ramayani, Oke Rina (Universitas Prima Indonesia, 2025)
Epilepsy in children has the potential to have a significant negative impact on cognitive function, with a high risk of attention deficits and impaired executive function. Quality of life has been associated with cognitive performance, especially in verbal memory, which is one of the domains most sensitive to the negative effects of epilepsy. The purpose of this research is to know connection quality Sleep with emotional on pediatric patients with epilepsy. This study is an observational analytical study conducted at Haji Adam Malik General Hospital, Medan from August 2024 to September 2024. Calculation big sample use formula big non-experimental correlative sample based on previous studies, which produced a minimum sample size of 25 samples. The collected data was processed and analyzed univariately to describe the characteristics of the research respondents. The results showed that the subjects of the study were 6 (20.0%) children and 24 (80.0%) adolescents. Male gender 17 (68.0%) and female 8 (32.0%). Toddler age 5 (20.0%), childhood 16 (64.0), and early adolescence 4 (16.0%). Disturbed sleep quality 15 (60.0%) and undisturbed sleep quality 10 (40.0 %). Emotional disturbance 21 (84.0%) and sleep behaviour 4 (16.0%). Mean sleep duration 7.54 hours, minimum 6 hours, and maximum 10 hours. concluded that, the prevalence of sleep disorders in children with epilepsy at RSUP H. Adam Malik Medan was male 17 (68.0%), duration sleep has an average of 7.54 hours, sleep quality was disturbed there were 15 (60.0%), and disturbances emotional was disturbed by 21 (84.0%).